A proposed taxonomy for literature review in multi-objective vehicle routing problems - Martin, Iris; Wibisono, Eric (AIP conference proceedings, 2024)
Vehicle routing problems deal with determining the routing of a fleet of vehicles under a set of constraints to serve geographically dispersed customers. The problems belong to a subset of combinatorial optimization problems and are widely studied due to their academic appeal and numerous applications. The classical version of this subject usually minimizes a single objective in total distance or total cost. However, given that many real-life problems are inherently multi-objective, a variant that considers multiple objectives is getting more attention nowadays. The latest review in this area was in 2008 and more than a decade has now elapsed with the absence of similar study. The objectives of this paper are to summarize the selected new research of multi-objective vehicle routing problems that span beyond 2008 and to propose a taxonomy that can be used to categorize the studies in this area. The proposed taxonomy includes eight criteria covering identification and characteristics of the papers. The findings from the review suggest tendencies toward certain scopes such as time windows formulation (VRPTW), the development of population-based algorithms especially the genetic algorithm and elitist non-dominated sorting genetic algorithm (NSGA-II), and the use of Solomon benchmark instances in the numerical experiment.